Design of Data Acquisition System for Silicon Micro Machined Resonant Accelerometer. (January 2019) - Xu, Yun; Qu, Yaohui; Luo, Zhihang
Abstract: The output of the silicon micro machined resonant accelerometer is a frequency signal, in which the measured acceleration has been converted. Thus, it can realize a better performance. The output of the silicon micro machined resonant accelerometer in this paper is the differential frequency signal. The resolution of it is ±1mg, the scale factor is100Hz/g, the measuring range is ±50g, and the resonant center frequency is 20 kHz. Aiming at the above technical indexes, and based on multiple-period synchronous method, the data acquisition system is designed in this paper. The data acquisition system contains the signal shaping module, the counter module, and the microcontroller and the communication module. The test experiment shows that the designed data acquisition system can satisfy the measurement requirement of the silicon micro machined resonant accelerometer.